Therapeutic Drug Monitoring of Tumor Necrosis Factor Antagonists in Crohn Disease: A Theoretical Construct to Apply Pharmacokinetics and Guidelines to Clinical Practice. Issue 8 (14th October 2020) - Vande Casteele, Niels; Feagan, Brian G; Wolf, Douglas C; Pop, Anca; Yassine, Mohamed; Horst, Sara N; Ritter, Timothy E; Sandborn, William J
Abstract: Therapeutic drug monitoring (TDM) is the measurement of drug and antidrug antibody concentrations in individuals to guide treatment decisions. In patients with Crohn disease (CD), TDM, used either reactively or proactively, is emerging as a valuable tool for optimization of tumor necrosis factor (TNF) antagonist therapy. Reactive TDM is carried out in response to treatment failure, whereas proactive TDM involves the periodic monitoring of patients responding to TNF antagonist therapy to allow treatment optimization. In patients with CD, most of the available data for TDM relate to the first-to-market TNF antagonist infliximab and, to a lesser extent, to adalimumab and certolizumab pegol. Several gastroenterology associations, including the American Gastroenterology Association, have endorsed the use of reactive TDM in patients with active CD. However, fewer recommendations currently exist for the use of proactive TDM, although several new prospective randomized controlled trials evaluating proactive TDM strategies have been published. In this review, the current evidence for reactive and proactive TDM is discussed, and a proactive treatment algorithm for certolizumab pegol based on previously published threshold concentrations is proposed.